Education and human dignity - intersection of paths - Hickenbick, Claudia (2017)
This paper describes the Pedagogical Political Project of the Integration Committee on Social Programs of the Federal Institute of Education, Science and Technology of Santa Catarina - IFSC, Brazil. The methodology used in developing the project was to foster the creation of four pilot projects which enabled reflections about institutional adequacy in the offering of Youth and Adult Education (EJA). As a result, an alternative interpretation was outlined of the concept of human dignity related to the power that can be attributed to education for workers that includes recognition of knowledge (CERTIFIC), education elevation (PROEJA) and vocational education as alternative social and personal development for those who have not had the opportunity to enjoy, at the so-called "appropriate" age, the basic right to education.